COVID-19 WORKING FROM HOME IS EQUALLY PRODUCTIVE AS WORKING FROM OFFICE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
COVID -19 lockdown has and continues to shape the world of work. Working from home became popular after the Ghana government put a statewide restriction on people's movement and a full lockdown in Accra, the capital, and Kumasi, the second largest city. The COVID-19 pandemic continues to shape the world of work. It caused many workers in Ghana to work from home for the first time. This study examined the productivity of working from home during the COVID-19 pandemic using one sample t-test. It sampled a total of 355 respondents in the Greater Accra and Greater Kumasi of Ghana to examine their level of productivity. The findings show that COVID-19 inducted working from home is equally as productive as working from office.